HEMATOLOGICAL EFFECTS OF DICLOFENAC SODIUM IN GOAT - Ahmad; I.; T. A. Qureshi; U. Sadique; S. A. Khan; S. Ahmed; Z. U. Rehman; S. Bahadar; M. Mushtaq (Journal of Animal and Plant Sciences, 2013)
Diclofenac sodium is commonly used as an analgesic, anti-inflammatory and ant rheumatic agent. In addition to its beneficial effects diclofenac has also been reported to be associated with some adverse effects. In this study hematological effects of diclofenac sodium were studied. The drug was administered in six goats, in two phases with adequate wash out period of 21 days between each phase. In phase-1 diclofenac was administered in all animals with 2.5 mg/kg body weight and in phase-2 with 1 mg/kg dose rate. Blood parameters altered significantly only with the high dose (2.5 mg/kg) of diclofenac sodium. red blood cells was significant decrease (P<0.05) at 12 hours and hemoglobin (at 6 and 12 hours) was observed with the high dose of the drug. A significant increased P<0.05) was detected in WBCs count at 6, 12 and 24 hours post high dose of diclofenac. Granulocytes decreased significantly (P<0.05) at 6 and 12 hours post high dose administration. Monocytes and lymphocytes increased significantly (P<0.05) with high dose of diclofenac at 6,12,24,48 and at 12 and 24 hours respectively. Decreased (P<0.05) platelets count was marked at 12 and 24 hours post diclofenac administration. It has been concluded that high dose of diclofenac sodium significantly affect blood cell count and the effects are drug related and subside 72 hours post drug administration.
Keywords: Non steroidal anti – inflammatory drugs (NSAID); red blood cell; white blood cell; platelets; diclofenac sodium; goat